Development of anesthesia nursing in the world and in Poland - Ulenberg, Grzegorz; Ulenberg, Agata; Grabowska- Gaweł, Anna; Czapiewski, Łukasz; Dąbrowska, Maria; Smyk, Paulina; Lewandowska, Anna (Journal of Education, Health and Sport, 2017)
Anesthesiology is a branch of medicine that covers all aspects of the fight against pain, associated diseases, injuries or malformations in the 50 - of the twentieth century began with the dynamic development of anesthesia in Europe. New specializations have emerged that have not missed nursing. Anesthesia was administered by most of the specialists in the field of nursing of instrumentalists. At that time, nurses were also separated, who only dealt with the administration of anesthesia.